The Implementation of Inter-Agency Task Force Safety Protocols for Wet and Dry Market in Barangay 177 Camarin, Caloocan City: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers want to determine if the safety protocols implemented by the Inter-Agency Task Force (IATF) are being strictly followed in the market to help break the transmission of the virus. Wet and dry markets sell affordable and locally produced fresh foods essential for peoples' economic growth and livelihood. Poor hygiene is a major risk factor for human health in wet markets. Many safety protocols are implemented by the Inter-Agency Task Force (IATF) to strengthen food safety practices and enhance hygiene and sanitation practices. When the pandemic spread, many businesses were affected, so the Inter-Agency Task Force (IATF) implemented protocols in each market to prevent the spreading of the virus, such as wearing facemasks and face shields, maintaining physical distancing, limiting the to go to the market and each person is allowed to enter the market to reduces the chance of being exposed to the possible contamination.  The researchers used the descriptive method mixed with a phenomenological approach. The descriptive method is the design used by the researchers to find information about existing conditions. The researcher’s goal is to employ this method to describe the nature of the real situation as it exists at the time of the study.  The researchers conducted survey questionnaires with the consumers, vendors and law enforcers. The questionnaire is the primary tool for gathering data to respond to the problem raised. In this method, written responses were given to prepared questions intended for the respondents to reply. Questions were developed to be easily understood by the respondents. The study concluded that based on the demographic profile of the three groups of respondents’ consumers, vendors and law enforcers. Most consumers were 34-41 years old, female, single and high school graduates. In contrast, most vendors were 26-33 years old, male, single and high school graduates. Lastly, most law enforcers were 42-50 years old, female, married and vocational, high school level, college level and college graduate. In the assessment, the community follows safety protocols such as maintaining social distancing and wearing facemasks and face shields. A healthy business operation can be achieved by having maintenance such as monitoring and reporting of employees' health such as contact tracing, reporting it to the LGU after the quarantine period, and they can return to work as they have the negative result in COVID testing. The frequent problem customers encounter is the failure to follow social distancing when they enter the market. As assessed, posting a regulation sign in front of the store is the respondents' most rated measure that may be proposed to address the problem. The recommendations proposed by the researcher to avoid violating the implemented safety protocols were rated as highly recommended.